A COMPARATIVE STUDY OF HSP70 GENE EXPRESSION FOR FIVE SPECIES OF ROSA L. - Jazaa , Liqaa A.; Alwash, Bushra M. J. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
This study was aimed to compare and evaluate the increasing or decreasing levels of Hsp70 gene expression of five species of Rosa L, 1735 (the most popular ornamental plant that extended throughout the global with high economic value and great cultural importance), Rosa canina, Rosa damascena, Rosa centifolia, Rosa hybrida and Rosa xanthine through total RNA extraction from plant leaves for the five species then reverse-transcribed to complementary DNA (cDNA) then amplified by RT-qPCR technique as a relative quantitation method .The results demonstrated that gene expression of HSP70 was varied between two seasons, spring and summer seasons. The highest gene expression of HSP70 for the R. canina in summer season was recorded at 1.0000 gene fold and 22.950 Ct value as compared with other treated species show low fold of gene expression (0.0012 - 0.0983) gene folding . Our conclusion is that HSP70 elevated levels of gene expression is crucial for heat stress tolerance precisely in R. canina enabled to maintain maintain vegetative growth and flowering throughout the year